Welding Joint Analysis On Three Wheel Transport Ambulance Frame - Wilujeng, Auliana Diah; Fatah, Misbakhul; Abdi, Ferly Isnomo; Sufi, Achmad Hikam Ulul (Universitas Muhammadiyah Metro, 2025)
Three-wheels ambulance transport is crucial for the mandangin island community, sampang subdistrict, sampang regency. The construction of a three-wheel ambulance utilizes the frame of a typical three-wheeled vehicle. However, according to technical guidelines for ambulance vehicles, the required length exceeds that of the standard three-wheel vehicle. Therefore, the frame of the three-wheel vehicle is extended using additional materials to increase the vehicle's length. The frame extension method employed is welding. Two welding path variations are used: straight and zig-zag. Testing was conducted using SolidWorks simulation and validated through bending tests. The simulation results indicated a stress value of 248 MPa for both variations. Meanwhile, the validation tests produced stress values of 66.99 MPa for the straight weld path and 69.42 MPa for the zig-zag weld path. This demonstrates a significant difference in stress between the simulation and validation results, attributed to residual stresses and distortion changes after welding. Additionally, the variation in welding paths (which may affect weld length) did not yield significant differences in outcomes